Setting the three-stage R&D shared portfolio methodology: an innovative approach to industry–university collaboration (REGE Revista de Gestão, 2023)
Purpose – The purpose is to present an approach to start industry-university (I-U) collaboration through a phased process aimed at building a portfolio of Research and Development (R&D) projects.Design/methodology/approach – It devises from an 18-month action-research program held between a multinational automotive manufacturer and a top-ranked Brazilian university.Findings – The 3-Stage RSP methodology results from a combined application of QFD-like (Quality Function Deployment) correlation matrices and Roadmapping. The first matrix tackles industry interests and correlates product performance dimensions and components to reveal broad research areas of interest. A second matrix correlates research areas and engineering competences, highlighting the types of required know-how from the university standpoint. Thirdly, academic experts help to fill a roadmap-like layer with possible collaborative R&D deliverables over time.Research limitations/implications – As the study lies on a single experience, extensions to other contexts should be made with caution. However, the proposal offers a robust rationale and a set of supporting tools to nurture new applications.Practical implications – Theoretical and methodological reflections help managers tackle the long-standing problem of setting a shared R&D agenda.Originality/value – Literature on industry-university collaboration tends to over-emphasize the role of Technology Transfer Offices in promoting the partnerships, or to seek implications for public policy. This research offers a valuable approach to building a shared R&D project portfolio from a managerial viewpoint, filling an academic gap and offering guidance for managers on both sides.